Assessment of Efficacy of 2D Echo and Contrast Echo in Detection of Thrombus. - Razdan, Monica; Chouhan, Bhupendra (Asian Journal of Medical Research, 2019)
Background: As echo is widely used to screen patients with coronary disease or heart failure at risk for LV thrombus, optimization of diagnostic strategies for thrombus detection is of substantial importance. Hence; we planned the present study to assess and compare the efficacy of 2D echo and contrast echo in detection of thrombus. Subjects and Methods: The present study included assessment and comparison of 2D echo and contrast echo in detection of thrombus. A total of 25 patients were included in the present study. Detailed demographic data and biochemical profile of all the patients was obtained. All the patients underwent both 2D echo and contrast echo. All the results were compiled in Microsoft excel sheet and were analysed by SPSS software. Results: 2D echo detected thrombus in 3 percent of the cases while the contrast echo detected thrombus in 12 percent of the cases. Significant results were obtained while comparing the prevalence of thrombus as detected by 2D echo and contrast echo. Conclusion: Efficacy of contrast echo s significantly higher than that of 2D echo in detecting LV thrombus.